Foliar application of chitosan and titanium dioxide enhances silybin content by orchestrating miRNA and gene targets transcription in Milk thistle (Silybum marianum L.) - Jafari, Samira; Mousavi-Fard, Sadegh; Rezaei Nejad, Abdolhossein; Mumivand, Hasan; Sorkheh, Karim; Nikoloudakis, Nikolaos (My University, 2023)
Milk thistle (Silybum marianum L. Gaertn.) is an important herbaceous and annual plant that is used as a pharmaceutical for the remedy and prevention of liver diseases. Till now, there have been no reports of miRNAs’ involvement in the production of secondary metabolites in milk thistle. The present study was conducted with the aim of investigating the foliar application of chitosan and titanium dioxide (bulk and nano forms) on seed silybin content and the crosstalk of miRNAs and target genes. The ideal formulation [bulk and nanoparticles (NPs)] and concentration (0–100 mg L−1) of titanium dioxide and chitosan applications for upregulating seed silybin content were investigated across ﬁve ecotypes. Additionally, the expression of miRNAs and their target genes involved in silybin biosynthesis were evaluated. Data revealed that foliar application of elicitors increased the content of silybin A, silybin B, and total silybin in all five ecotypes. The cultivar 'Budakalazi' had the best response compared to other ecotypes. The application of chitosan and TiO2 decreased the expression of all five miRNAs in the phenological stage of immature seeds. In contrast, target gene expression was generally upregulated. miRNAs expression was generally linked to the phenological stage of mature seed, as miR156b, miR1438, and miR157a-5p were over-expressed, while miRNAs miR1873 and miR829.1 were down-regulated. In general, foliar application of Nano chitosan, especially at a concentration of 50 mg L−1, increased the amount of silybin content by reducing the expression of most miRNAs, and upregulating the transcription of their target genes involved in silybin biosynthesis.
Keywords: Budakalazi; Elicitors; Micro-RNAs; Secondary metabolites; Target genes; TiO2